Technostress, psychosocial safety climate, and worker well-being in automated manufacturing: A two-wave study - Umut Elbir; Kagan Cenk Mizrak (PLoS ONE, 2026)
The rapid digitalization of manufacturing has introduced new psychosocial risks alongside productivity gains, particularly in the form of technostress. This study investigates how technostress influences worker mental health, burnout, engagement, and safety outcomes in automated manufacturing environments, and whether job resources and psychosocial safety climate (PSC) serve as protective factors. Drawing on the Job Demands–Resources (JD-R) model, a two-wave panel design was employed with data collected from 605 employees at baseline and 450 employees at a four-week follow-up across five automated manufacturing plants. Multilevel and moderation analyses revealed that while direct effects of technostress on outcomes were directionally consistent with theoretical expectations, they were not statistically significant. Instead, job resources—including supervisory ICT support, recovery opportunities, and digital literacy—emerged as significant buffers, mitigating the potential negative effects of technostress. Furthermore, PSC at the crew and organizational level predicted improved engagement, better mental health, and stronger safety behaviors, underscoring its role as a higher-order organizational resource. These findings suggest that technostress in manufacturing is contingent on contextual factors: it becomes harmful when resources are insufficient and protective climates are absent. The study contributes to technostress and occupational health literature by integrating psychosocial and technological stressors in a multilevel framework and offers practical guidance for managers seeking to balance digitalization with worker well-being.